Infection of capacity of Beauveria bassiana (nativa) on the chinches complex of the crop of Chenopodium Quinoa in the irrigation Majes 2018 - Dina Beatriz Mamani Gutierrez (2019)
The present research work was developed in the field of research (CRA) and in the laboratory of the AUTODEMA in Majes Irrigation in 2018, in order to evaluate the infection capacity of Beauveria bassiana (native) as microbiological controller of the bugs of quinoa cultivation in Majes Irrigation; being the main objective of the investigation. In order to carry out this experiment, conidia of Beauveria bassiana (native) were obtained from bed bugs from quinoa fields of the Majes Irrigation; making the direct isolation of the fungus until the artisanal production of this one. To evaluate the infection capacity of the fungus in question, a solution application was made with the entomopathogen, for which after the application, insect samplings were made for a period of 7 days after the application. These specimens were placed in nursery boxes and after their death they were placed in a humid chamber to see if they were infectedor not by Beauveria bassiana (native). The results obtained indicate that Nysius sp. it is more susceptible than Liorhysus sp. to be infected by the entomopathogen is study. It is observed that in immature stages (nymph) have a greater pathogenicity, since, 42.86% mortality was obtained. Unlike adults where there is greater tolerance to infection of Beauveria bassiana (native), obtaining 33.33% mortality.